Regional Study on the Management, Control, and Recording of Fixed Assets : Latin America and the Caribbean - Gourfinkel, Dmitri (World Bank, Washington, DC, 2017)
This report represents a series of studies on the status of the implementation of the International Public Sector Accounting Standards in the Latin America region. The first report of this series, Public Sector Accounting and Financial Information in Latin America, was developed by the World Bank team and issued in April 2015. The general purpose of this second report is to document the status of the management, control, and recording of fixed assets in the countries surveyed, and to propose a comprehensive asset management model to strengthen the region’s public financial management systems in terms of public sector accounting, public investment, transparency, and accountability. The report aims to address the following asset management challenges: (a) accounting methodologies that have been adopted or implemented in the surveyed countries do not necessarily capture all government fixed assets; (b) incomplete or unreliable information on infrastructure assets and projects and other fixed assets, as well as on the provisions related to their upkeep and replacement, creates obstacles to improving public investment policies and enhancing the region’s ability to promote productivity and competitiveness; (c) greater control of fixed assets is directly related to the improvement of transparency and accountability indexes; and (d) governments’ inability to obtain an objective picture of their financial position and performance limits the quality of analysis on the efficient use of public resources related to electoral commitments, fiscal stability, and economic growth in the medium and long term.